Sella Turcica Atypical Teratoid/Rhabdoid Tumor Complicated with Lung Metastasis in an Adult Female - Costanzo Moretti; Domenico Lupoi; Francesca Spasaro; Laura Chioma; Paola Di Giacinto; Martina Colicchia; Mario Frajoli; Renzo Mocini; Salvatore Ulisse; Manila Antonelli; Felice Giangaspero; Lucio Gnessi (Clinical Medicine Insights: Case Reports, 2013)
Here we present the case of a 60-year-old woman with a rare sellar region atypical teratoid/rhabdoid tumor (AT/RT), complicated by lung metastasis and treated with neurosurgery, radiotherapy, and chemotherapy. The patient had recurrent headache associated with left cavernous sinus syndrome after a previous endonasal transsphenoidal resection for a presumptive pituitary macroadenoma. Pituitary magnetic resonance imaging showed a tumor regrowth in the original location with a haemorrhagic component involving the left cavernous sinus. A near complete transsphenoidal resection of the sellar mass was performed followed by 3 months of stereotactic radiotherapy. Because of a worsening of the general clinical conditions, respiratory failure, and asthenia, the patient underwent a contrast enhanced computer tomography of the whole body which showed the presence of lung metastasis. The histopathological diagnosis on samples from pituitary and lung tissues was AT/RT. The patient survived 30 months after diagnosis regardless chemotherapy. In the adult, the AT/RT should be considered as a possible rare, aggressive, and malignant neoplasm localized in the sella turcica.